Investigation of Platinum-Catalyzed Acylation of 2-Aryloxypyridines via C-H Activation and Functionalization - Barham, Alex (East Carolina University, 2022)
Transition metal catalyzed C-H activation and functionalization reactions allow synthetic chemists to break the normally unreactive carbon-hydrogen bond and create a new and useful carbon-oxygen, carbon-nitrogen, carbon-halogen, or carbon-carbon bond. C-H activation and functionalization reactions were originally used for the transformation of methane gas to methanol. However, C-H activation and functionalization has shifted from the conversion of hydrocarbons to a more practical use such as the synthesis of complex organic molecules. The Huo group recently discovered a novel platinum-catalyzed selective C-H acylation method that introduces an a-keto ester, in the ortho-position of 2-aryloxypyridines. The reaction is oxidant and additive-free, while also withstanding decarbonylative side reactions. To gain further insight into this novel reaction, possible reaction steps involved in the catalytic cycle were investigated (Figure 1). The key steps investigated include ligand exchange of the ligand, L1, with the pre-catalyst cis- and trans-Pt(PhCN)2Cl2, the rate of intramolecular C-H activation (cyclometallation), and the acylation of the trans-cyclometallated complex. It was found that all cis- complexes, including the pre-catalysts, exhibited higher catalytic activity in the C-H acylation reaction of 2-(2-methylphenoxy)pyridine. The results of these reactions and their significance will be discussed. To deepen our understanding of the applicability of this novel Pt-catalyzed reaction, the Huo group decided to investigate the tolerance of this reaction with the use of other acylating reagents such as 2-(diethylamino)-2-oxoacetyl chloride to introduce an a-keto amide functional group. The Pt-catalyzed reaction successfully introduced the a-keto amide functionality in the ortho-position of 2-aryloxypyridines. Figure 1. Multiple reaction pathways involved with the Pt-catalyzed C-H acylation of 2-(2-methylphenoxy)pyridine, L1, with ethyl chlorooxoacetate to produce the acylated product L2.
Keywords: Inorganic chemistry; Catalysis